Technological learning, policy regimes and growth in a "globalized" economy: General patterns and the Latin American experience - Carolina Castaldi; Mario Cimoli; Nelson Correa; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
The aim of this work is to investigate the role played by the so-called 'globalization' processes of the last couples of decades on the international patterns of technological learning and on the distribution of incomes and growth. First, we re-assess the evidence on the general patterns of the current globalizing'' tendencies at various levels of observation and we argue that 'globalization' has not gone together with international convergence in technological capabilities and incomes. We also focus on trends related to the 'ICT revolution' and we highlight the relevance of 'retardation factors' in explaining the rather limited impact of this new techno-economic paradigm. The last couple of decades have also witnessed the international diffusion (or, more often, the imposition) of laissez-faire policy regimes. Their revealed impact upon technological learning and growth, however, is at best mixed, or straightforwardly negative. We exploit the case of Latin American countries to study the dramatic effect of liberalization policies. We show how these policies may produce a 'vicious growth path' when a country is not able to decrease its technology gap and improve its trade balance at the same time. Indeed, the general evidence and the lessons learnt from the Latin American experience both powerfully hint at the continuing role of public policies in fostering the accumulation of technological knowledge and its economic exploitation. We suggest some taxonomies of the 'control' and 'state' variables which policies are likely to influence. We argue that policy making still has unexploited degrees of freedom and we suggest that one way to go is re-thinking the role of international and domestic markets.
Keywords: 330; Technischer Fortschritt; Lernprozess; Globalisierung; Einkommensverteilung; Innovationsdiffusion; Wirtschaftswachstum; Wirtschaftsreform; Lateinamerika; New Economy